Validation of the Japanese version of the revised version of the compound psychological capital scale (CPC-12R) - Ikeda, Megumi; Hatano, Kai; Tanaka, Satoshi; Nakahara, Jun (Frontiers in Psychology, 2023)
This study developed a Japanese version of the Revised Version of the Compound Psychological Capital Scale (CPC-12R) and tested its reliability and construct validity. The participants were 1,000 young adults (500 university students and 500 employees) recruited through an internet survey. Confirmatory factor analysis showed that the four first-order factors (hope, optimism, resilience, and self-efficacy) and one second-order factor (PsyCap) model of the previous study is appropriate for the Japanese context. In addition, Cronbach's α and omega-higher-order of CPC-12R were sufficient. The measurement invariance analysis suggested sufficient scalar invariances for the employees and university students and across genders. The Japanese version of the CPC-12R had moderate positive correlations with job satisfaction, work engagement, conscientiousness, and extraversion, as well as a moderate negative correlation with negative emotionality. These findings provide evidence for sufficient reliability and construct validity of the Japanese version of the CPC-12R.